Comment on: Development and validation of a novel nomogram for predicting the occurrence of myopia in schoolchildren: a prospective cohort study - Lança, Carla (2023)
In the recent article published by Guo et al., the authors used data from 2nd and 3rd graders to develop a nomogram to predict myopia onset in schoolchildren. Given that myopia can progress to high myopia, which is in turn a risk factor for pathologic myopia, prediction tools are timely and relevant. We would like to provide insights into other limitations and offer suggestions that can inform future works.